2021
DOI: 10.1111/1471-0528.16849
|View full text |Cite
|
Sign up to set email alerts
|

The psychological impact of gestational trophoblastic disease: a prospective observational multicentre cohort study

Abstract: Objective To evaluate the short-term psychological consequences of gestational trophoblastic disease (GTD).Design A prospective observational multicentre cohort study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
0
10
0
2
Order By: Relevance
“…139 In a prospective study published in 2022 of the psychological impact of GTD on 60 women, 47% reported feeling anxious and 70% reported feeling distressed during the surveillance period. 140 Unfortunately, this study did not record previous mental health status or antidepressant use of the participants which was highlighted in a follow-up letter to the editor. 141 142 A survey of women on the Irish national GTD registry found that women experienced feelings of intense sadness at the time of diagnosis and needed psychological support to help them to deal with the pregnancy loss.…”
Section: Open Access Open Accessmentioning
confidence: 98%
“…139 In a prospective study published in 2022 of the psychological impact of GTD on 60 women, 47% reported feeling anxious and 70% reported feeling distressed during the surveillance period. 140 Unfortunately, this study did not record previous mental health status or antidepressant use of the participants which was highlighted in a follow-up letter to the editor. 141 142 A survey of women on the Irish national GTD registry found that women experienced feelings of intense sadness at the time of diagnosis and needed psychological support to help them to deal with the pregnancy loss.…”
Section: Open Access Open Accessmentioning
confidence: 98%
“…Despite such a high cure rate, GTN patients still have to face the pressure of pregnancy failure, surgery, possible chemotherapy management, chemoresistance, chemotherapy toxicities, relapse, and delayed future fertility, not to mention late mortality. Due to immediate and long-term stress, patients with GTN may experience psychological, social, and sexual stress apart from physical pain [3]. Accompanied by the distress mentioned above, psychological, social, and sexual problems may occur silently.…”
Section: Sciences (Spss)mentioning
confidence: 99%
“…Furthermore, a positive correlation had been found in the scores between HADS-A and HADS-D (r = 0.77, ρ< 0.001), while the analogous relationship didn't exist in HADS-A (r= 0.09, ρ= 0.45) and HADS-D (r = 0.06, ρ= 0.61) with SWLS.Conclusions: Our work herein suggests that various characteristics, especially the status of treatment, surgical treatment, and place of residence were central to psychological complaints such as anxiety, depression as well as satisfaction in GTN patients.Despite such a high cure rate, GTN patients still have to face the pressure of pregnancy failure, surgery, possible chemotherapy management, chemoresistance, chemotherapy toxicities, relapse, and delayed future fertility, not to mention late mortality. Due to immediate and long-term stress, patients with GTN may experience psychological, social, and sexual stress apart from physical pain [3]. Accompanied by the distress mentioned above, psychological, social, and sexual problems may occur silently.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We have read the study by Liang et al, 1 and wanted to congratulate the authors on their valuable article and to make some minor contributions.…”
Section: Sirmentioning
confidence: 99%